Does Breast Milk Affect Neonatal Abstinence Syndrome Severity, the Need for Pharmacologic Therapy, and Length of Stay for Infants of Mothers on Opioid Maintenance Therapy During Pregnancy?. (October 2016) - Cirillo, Cheryl; Francis, Kim
Abstract : Background: The United States is in an opioid crisis with abuse among women on the rise over the past 10 years. Infants of opioid-dependent mothers are at risk for neonatal abstinence syndrome (NAS). Neonatal abstinence syndrome can affect multiple systems and disrupt normal growth and development. It is for this reason that strategies to promote health such as breastfeeding need to be explored. This brief evaluates current evidence regarding breast milk and the impact it has on NAS. Purpose: The question guiding this brief is: "Does provision of breast milk reduce NAS withdrawal symptoms, decrease length of stay, and decrease the need for pharmacologic therapy for infants whose mothers are maintained on methadone or buprenorphine?" Search Strategy: CINHAL/MEDLINE Complete and PubMed databases were searched using key words—NAS and breastfeeding—and the search was limited to 10 years for English studies evaluating the effects of breast milk on severity of NAS, pharmacologic therapy, and length of stay whose mothers received methadone or buprenorphine during pregnancy. The search yielded 10 studies addressing these concerns. Findings: Breast milk may be beneficial for decreasing NAS severity, pharmacologic therapy, and length of stay. Implications for Practice: Strategies should be developed to support individualized plans based on maternal history, safety, and mother's choice. Implications for Research: Further research is needed utilizing matched case-controlled studies regarding breast milk and the influence on severity of NAS, need for pharmacologic therapy, length of stay, and neurologic outcomes. In addition, other factors should be investigated including abrupt weaning, polysubstance use, and readmissions.